Narrative Analysis in Bayer Leverkusen’s Journey to Champion Youtube Review Video - Rahayu, Dwi; Akbar, Muhammad Zikri; Dzaki, Muhammad Haekal; Hidayah, Lutfiana Zalfa (Jurnal Sasindo UNPAM, 2024)
This study aims to recognize the types of narratives contained in a video that tells the story of Bayer 04 Leverkusen's journey in winning the Bundesliga title for the 2023/2024 season. The video was published through the Bundesliga's official channel on YouTube with the title "Xabi Alonso Leverkusen Road to the Champions." The approach used in this research is qualitative, focusing on identifying the narrative structure and data revealed in the video. Labov’s (2001) theory served as a foundation to explain the framework of the problem to analyse how the story in the video is structured, from the introduction to the culmination of conflict and resolution, and how narrative elements such as plot, character, and atmosphere are used to form a strong narrative. The findings indicate insight into how stories about the achievements of a soccer team can be presented through visual media such as YouTube. By analysing the narrative structure and data in the videos, this research can provide a more comprehensive picture of how video makers use narrative elements to build stories that attract and captivate audiences.